2016
DOI: 10.1002/lno.10450
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic and mixotrophic nanoflagellates in a mesotrophic lake: Abundance and grazing impacts across season and depth

Abstract: Nanoflagellates are recognized as fundamental members of the planktonic microbial food web due to their contribution to photosynthetic fixation of carbon and phagotrophic ingestion of bacteria. Although the presence, and often dominance, of mixotrophic nutrition among phytoflagellates has been well documented within a variety of aquatic ecosystems and in a range of taxa, few studies have assessed the abundance and grazing impact of mixotrophs in comparison to their photosynthetic and heterotrophic counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…To obtain predator diversity estimates, we extracted the OTUs from the 18S rDNA pool that was affiliated to the common bacterivorous nanoflagellates according to the literature ( Supplementary Table S1), which contained mostly the heterotrophic nanoflagellates (HNF). Although a number of pigmented nanoflagellates are bacterivorous (known as mixotrophic nanoflagellates), we did not include them in the predator assemblages, given controversy surrounding the extent to which these groups contribute to the top-down control on bacterial communities [62][63][64][65].…”
Section: Estimating Predator and Prey Diversitymentioning
confidence: 99%
“…To obtain predator diversity estimates, we extracted the OTUs from the 18S rDNA pool that was affiliated to the common bacterivorous nanoflagellates according to the literature ( Supplementary Table S1), which contained mostly the heterotrophic nanoflagellates (HNF). Although a number of pigmented nanoflagellates are bacterivorous (known as mixotrophic nanoflagellates), we did not include them in the predator assemblages, given controversy surrounding the extent to which these groups contribute to the top-down control on bacterial communities [62][63][64][65].…”
Section: Estimating Predator and Prey Diversitymentioning
confidence: 99%
“…The important role of pigmented nanoflagellatesas important bacterial consumers has been demonstrated in previous studies [6,8], but their significance in regulating bacterial communities is still under discussion. PNFs are also important Synechococcus grazers in marine environments [15].…”
Section: Introductionmentioning
confidence: 96%
“…Although grazing by heterotrophic nanoflagellates is showed by top-down control in the bacterial communities, pigmented nanoflagellates (PNFs) have been considered as important bacterivores in planktonic food webs in recent studies [6][7][8]. Some field studies observed that in marine and freshwater systems, PNFs outnumber the heterotrophic nanoflagellates, and thus have a greater grazing impact on the bacterial community [6,[8][9][10]. PNFs can survive in different environments by relying on bacterivory during low-light conditions, darkness, dissolved nutrient concentration, and photosynthesis when prey concentration is low [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the diversity and community composition of aquatic protistan communities (i.e., unicellular eukaryotes) have been well studied using DNA sequencing methods (Simon et al, 2015;Filker et al, 2016;Debroas et al, 2017). However, their temporal dynamics have been studied mostly on short timescales, i.e., from days to seasons (Debroas et al, 2015;Mukherjee et al, 2017;Princiotta and Sanders, 2017), and rarely over timescales relevant to investigate their responses to inter-annual variability (except Cram et al, 2015 for marine bacterial communities) or longerterm pressures. The longest DNA-based monitoring time serieswhich extend up to one decade (e.g., BATS, HOT, SPOT and BBMO; Fuhrman et al, 2015;Giner et al, 2018) -have been useful to identify day length (e.g., luminosity) and temperature as major drivers of community turnover.…”
Section: Introductionmentioning
confidence: 99%